Stable isotope tree-ring records (Tungsten, Northwest Territories, Canada) 1900- 2003 - Andreu-Hayles, Laia; Oelkers, Rose (NSF Arctic Data Center, 2021)
Stable isotope tree-ring records spanning from 1900 to 2003. The isotopic measurements were done using tree-ring samples from a white spruce (Picea glauca [Moench]Voss) forest located at 1145 meters above sea level (m a.s.l) near Tungsten (61.98º North (N); -128-25º West (W)) in the Northwest Territories, Canada. This stable oxygen isotope tree-ring record is mostly related to temperatures variations in spring and summer likely because it reflects the temperature imprint in the stable oxygen isotopes of precipitation. The tree-ring stable oxygen isotope tree-ring record also recorded similar correlation patterns than modeled precipitation delta-O-18 (δ18O) from the National Aeronautics and Space Administration (NASA) Goddard Institute for Space Studies (GISS) ModelE2 isotopically-equipped general circulation model (GCM). However, this shared patterns with significant positive correlations with surface temperature and geopotential height, but no correlations with moisture transport, only occurred in spring and summer when water matters more for trees. Overall, this stable oxygen isotope tree-ring record reflects the same significant large-scale climate patterns as stable oxygen isotopes in spring-summer precipitation and show great potential for reconstructing summer temperature variability and past atmospheric dynamics. The stable isotopes were generated at the Lamont-Doherty Earth Observatory (LDEO) of Columbia University (New York, United State of America (USA)) using the proceedings of cellulose extraction and measurements of stable isotopes described in Andreu-Hayles et al (2019). Andreu-Hayles, L., Levesque, M., Martin-Benito, D., Huang, W., Harris, R., Oelkers, R., Leland, C., Martin-Fernández, J., Anchukaitis, K.J. and Helle, G. (2019) A high yield cellulose extraction system for small whole wood samples and dual measurement of carbon and oxygen stable isotopes. Chemical Geology, 504, 53-65.